CRAI evolution or disruption: revisiting the model for academic libraries - Gallo-León, José-Pablo (Anuario ThinkEPI, 2023)
Through the Learning and Investigation Resource Centre (CRAI) model, Rebiun created a concept that has guided the organization, shape, and services of Spanish university libraries for the last 20 years. It was created for a reality different from the current one, and after two major crises, the need to revise it or move toward a new model that adapts to changing needs has arisen. After reviewing the most important trends, it is concluded that the CRAI model can still be valid if it is suitably modified.
Keywords: University libraries; Library buildings; CRAI; LRC; Future of libraries; Academic libraries; Rebiun